(untitled) (Detroit, 2008)
Alphabetically arranged encyclopedia (500 entries) that covers a wide variety of disorders, treatments, tests, and therapies, focused specifically on topics in mental health
Keywords: Psychiatry,Mental illness,Tâm thần học